2015
DOI: 10.1073/pnas.1514789112
|View full text |Cite
|
Sign up to set email alerts
|

The ancestral gene repertoire of animal stem cells

Abstract: Stem cells are pivotal for development and tissue homeostasis of multicellular animals, and the quest for a gene toolkit associated with the emergence of stem cells in a common ancestor of all metazoans remains a major challenge for evolutionary biology. We reconstructed the conserved gene repertoire of animal stem cells by transcriptomic profiling of totipotent archeocytes in the demosponge Ephydatia fluviatilis and by tracing shared molecular signatures with flatworm and Hydra stem cells. Phylostratigraphy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
115
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 67 publications
6
115
0
1
Order By: Relevance
“…http://dx.doi.org/10.1101/201103 doi: bioRxiv preprint first posted online Oct. 11, 2017; putative progenitor cells, which may underlie the regenerative properties of Nematostella (Passamaneck and Martindale, 2012). These cells were much less coherently associated than other clusters (Figure 1H), but they show expression of several factors associated with stemness (Alié et al, 2015; Hemmrich et al, 2012) (Figure S2).Comparison of the eight Nematostella broad cell clusters with published vertebrate organspecific transcriptomes (Brawand et al, 2011) revealed similarities between this neuronal cluster and vertebrate brain/cerebellum tissues (Figure S3A), as well as linkage between the contractile gastrodermis and muscle Nematostella tissues with vertebrate heart transcriptomes.Despite the vast evolutionary timescale separating Nematostella from vertebrates, several conserved effector genes, such as ion channels, synaptic components, and the neuron-associated RNA-binding protein ELAV show consistent co-expression that underlie these deep similarities ( Figure S3B). We expect richer comparative analyses will be dependent on much denser phylogenetic sampling of non-bilaterian and invertebrate bilaterian species.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…http://dx.doi.org/10.1101/201103 doi: bioRxiv preprint first posted online Oct. 11, 2017; putative progenitor cells, which may underlie the regenerative properties of Nematostella (Passamaneck and Martindale, 2012). These cells were much less coherently associated than other clusters (Figure 1H), but they show expression of several factors associated with stemness (Alié et al, 2015; Hemmrich et al, 2012) (Figure S2).Comparison of the eight Nematostella broad cell clusters with published vertebrate organspecific transcriptomes (Brawand et al, 2011) revealed similarities between this neuronal cluster and vertebrate brain/cerebellum tissues (Figure S3A), as well as linkage between the contractile gastrodermis and muscle Nematostella tissues with vertebrate heart transcriptomes.Despite the vast evolutionary timescale separating Nematostella from vertebrates, several conserved effector genes, such as ion channels, synaptic components, and the neuron-associated RNA-binding protein ELAV show consistent co-expression that underlie these deep similarities ( Figure S3B). We expect richer comparative analyses will be dependent on much denser phylogenetic sampling of non-bilaterian and invertebrate bilaterian species.…”
mentioning
confidence: 91%
“…The digestive filament cells, which represent the functional digestive elements of the animal, including epithelial and cilioglandular structures of the mesenteries, show expression a trp channel, a known mesentery-putative progenitor cells, which may underlie the regenerative properties of Nematostella (Passamaneck and Martindale, 2012). These cells were much less coherently associated than other clusters ( Figure 1H), but they show expression of several factors associated with stemness (Alié et al, 2015;Hemmrich et al, 2012) (Figure S2). …”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Ces approches ont également révélé certaines homologies entre le plan d'organisation des éponges et celui des eumétazoaires. Dans notre étude [5], nous nous sommes intéres-sés à l'origine des cellules souches en cherchant à reconstruire le répertoire de gènes ancestralement exprimés par ces cellules chez les animaux. Pour cela nous avons identifié des gènes homologues exprimés par les cellules souches d'éponges et celles d'autres lignées, afin de déterminer les innovations géné-tiques ayant accompagné l'acquisition de ce type cellulaire il y a 700 millions d'années.…”
unclassified
“…However, there is increasing acceptance that sponges are monophyletic (Philippe et al, 2009;Gazave et al, 2012;Worheide et al, 2012;Hill et al, 2013;Redmond et al, 2013;Thacker et al, 2013) and divided into four classes: Demospongia; Hexactinellida; Calcarea; and Homoscleromorpha (Gazave et al, 2012). In recent years, numerous resources have emerged from a wide range of sponge species including eight transcriptomes from all four classes (Riesgo et al, 2014), cell type transcriptome from the demosponge E. fluviatilis (Alié et al, 2015), and genomes and transcriptomes from the calcareous sponges Sycon ciliatum and Leucosolenia complicata (Fortunato et al, 2012;Fortunato et al, 2014a;Fortunato et al, 2014b), as well as the homoscleromorph Oscarella carmela (Nichols et al, 2012). Regardless of the precise phylogeny around and between sponges, they are an early branching metazoan phylum estimated to have diverged from eumetazoans approximately 650 to 800 million years ago (Berney and Pawlowski, 2006;Cohen et al, 2009;Lartillot et al, 2009;Parfrey et al, 2011; reviewed in Sharpe et al, 2015), making them an essential part of comparative analyses in investigating metazoan origins.…”
Section: Sponges As a Model System To Study The Origin Of Metazoan Mumentioning
confidence: 99%